2019
DOI: 10.1175/jpo-d-19-0020.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Abyssal Mixing on the Multilayer Circulation in the South China Sea

Abstract: By parameterizing the abyssal mixing as the exchange velocity (entrainment/detrainment) between the middle and deep layers of the South China Sea (SCS), its effects on the multilayer circulation are examined. Results indicate that the cyclonic circulation in the deep SCS appears only when the mixing induces an entrainment of at least 0.72 Sv (1 Sv ≡ 106 m3 s−1) from the deep to the middle layer, which is equivalent to a diapycnal diffusivity of 0.65 × 10−3 m2 s−1 or a net input rate of gravitational potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…mixing (approximately 10 −3 m 2 /s) in the deep ocean intensifies the abyssal circulation and the overturning circulation in the SCS (Quan & Xue, 2019;Tian et al, 2009; X. Wang et al, 2017).…”
mentioning
confidence: 99%
“…mixing (approximately 10 −3 m 2 /s) in the deep ocean intensifies the abyssal circulation and the overturning circulation in the SCS (Quan & Xue, 2019;Tian et al, 2009; X. Wang et al, 2017).…”
mentioning
confidence: 99%
“…For example, interactions between the TRWs and planetary Rossby waves probably account for the deep upwelling associated with meridional overturning circulation in the abyssal SCS (Shu et al., 2014). Moreover, TRWs and wave‐related mixing play a vital role in the generation and evolution of deep circulation in the SCS (Quan & Xue, 2019), as well as in the vertical coupling of the SCS circulation between the upper and middle layers (Quan & Xue, 2018). All these factors may lead to more active SCS circulation that could modulate the Indo‐Pacific exchange, thereby affecting the regional climate and ecosystem.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The Luzon Strait is the only deep channel connecting the SCS and western Pacific, with 2400 m maximum water depth. Cyclonic deep circulation is driven by the Luzon Strait overflow and intensified mixing in the deep basin of the SCS (Tian et al 2009;Wang et al 2011;Lan et al 2015;Gan et al 2016;Quan and Xue 2019). Previous studies have shown that the deep currents in the SCS exhibit strong intraseasonal variability, which is thought to be related to the Luzon Strait intrusion in the deep layer (Zhao et al 2014;Zhang et al 2014;Zhou et al 2017Zhou et al , 2020Ye et al 2019).…”
Section: Introductionmentioning
confidence: 99%